A role of bacteria in inflammatory bowel disease evoked in animal models - Strus, M; Uhlig, H; Powrie, F; Hornquist, E; Bland, P; Drzewiecki, A; Kochan, P; Gosiewski, T; Heczko, P (2005)
Introduction: Inflammatory bowel disease (IBD) encompass ulcerative colitis (UC) and Crohn's disease (CD). Their etiology is attributed to interactions between various genetic, immunologic and environmental factors but the nature of these interactions is not fully understood. Objectives: The elucidate the role of the bacterial flora in the pathogenesis of IBD in immunodeficient mice (Gαi2 and CB-17 SCID models). Material and methods: Immunodeficient mice and their controls, bred in identical conditions, were sacrificed and their G.I. tracts were excised. The intestinal content and the bacteria from the mucosal surface were cultured on appropriate media in aerobic and anaerobic conditions. Strain identification was performed using commercially available biochemical tests. Selected strains were additionally identified using PCR. The presence and the quantity of bacteria in tissue samples was estimated using fluorescent in situ hybridization (FISH). Results: In mice with IBD symptoms we noted an increase in bacteria from Lactobacillus genus as well as an increase of microorganisms from Enterobacteriaceae family. In animals of the control group the bacteria were only present on the surface of the mucus layer, whilst in animals with IBD the bacteria were found attached directly to mucosal cells. Conclusions: In this study we have shown that changes in the composition of the colonic flora may be related to the pathogenesis of IBD. Further investigations are needed in this field in order to be able to modify the course of IBD.